Diallel Analysis of Diverse Maize Germplasm Lines for Resistance to Aflatoxin Accumulation. Issue 2 (1st March 2013) - Henry, W. Brien; Windham, Gary L.; Rowe, Dennis E.; Blanco, Michael H.; Murray, Seth C.; Williams, W. Paul
ABSTRACT: In this study, diverse, novel maize ( Zea mays L.) germplasm from the Germplasm Enhancement of Maize (GEM) Project was screened to determine the combining ability and inheritance of ear rot resistance and resistance to aflatoxin accumulation in hybrid combinations. Nine GEM germplasm lines and six known resistant and susceptible inbred lines were selected as parents of a diallel cross that was evaluated over 2 yr at Mississippi State, MS, and 1 yr at College Station, TX. Resistant lines Mp717 and Mp494 each had negative and significant general combining ability effects, and were frequently present as parents in the hybrid combinations with the lowest aflatoxin accumulation. Of the GEM germplasm lines evaluated, GEMN‐0130 was the best source of aflatoxin resistance, with significant and negative GCA values at all three site years. The GEM lines exhibiting significant and negative GCA effects for aflatoxin accumulation in at least one site year include two GEM germplasm lines, GEMS‐0030 (2 yr) and GEMS‐0074 (1 yr), and a nonreleased GEM source derived from the tropical Cuban accession, CUBA117 (1 yr). The GEM germplasm lines significantly contributing to reduced ear rot in at least two out of three environments included CUBA117, GEMS‐0030, GEMS‐0002, and GEMN‐0130. These results demonstrate the GEM Project is a useful and untapped source of diverse germplasm for resistance to Aspergillus flavus ear rot and aflatoxin accumulation.